Model-Based Interpretation of PolSAR Data for the Characterization of Glacier Zones in Greenland - Parrella, Giuseppe; Hajnsek, Irena; Papathanassiou, Konstantinos (IEEE, 2021)
Different approaches have been proposed in recent years to map glacier zones using Synthetic Aperture Radar (SAR). Most of them rely on empirical or statistical approaches for the interpretation of backscatter intensity measurements and their seasonal variations related to the melting regime of the different glacier zones. This article focuses on the potential of polarimetric SAR measurements to characterize the scattering in the different glacier zones in order to distinguish between them. For this, a general two-component scattering model is proposed, accounting for surface and subsurface contributions in the different glacier zones. The (anisotropic) propagation through snow, firn, and ice layers is also accounted for as it plays an important role in the interpretation of the polarimetric signatures. A set of five polarimetric descriptors is proposed to describe the projection of the model on the SAR measurements. The ability of the model to characterize the scattering in the different glacier zones is validated and discussed at different frequencies (X-, C-, and L-band). For this, a multifrequency airborne SAR dataset acquired by the DLR's F-SAR sensor in West Greenland during the ARCTIC 2015 campaign is used. The achieved results indicate that L-band polarimetric measurements allow to differentiate the different glacier zones based on the subsurface (e.g., volume) scattering characteristics. In contrast, the increased (back-) scattering complexity and the reduced penetration capability limit the potential of X- and C-band polarimetric measurements. ISSN:1939-1404 ISSN:2151-1535